Preparation method of high-entropy alloy TPMS network enhanced TiAl-based composite material and application thereof

CN121669965BActive Publication Date: 2026-11-03GUANGDONG POLYTECHNIC NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511969730.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-24
Publication Date
2026-11-03
Estimated Expiration
2045-12-24

AI Technical Summary

Technical Problem

Traditional titanium alloys and nickel-based superalloys cannot simultaneously meet the requirements of high specific strength, specific stiffness and lightweight in extreme high-temperature environments. The brittleness of TiAl-based alloys and the segregation of Nb elements limit their engineering applications in complex components.

Method used

Selective laser melting technology was used to prepare the TiAlV0.5CrMo high-entropy alloy TPMS network structure, and combined with vacuum hot pressing sintering, a continuous and uniform reinforcing phase was formed, which optimized the material's microstructure uniformity and interfacial bonding strength.

Benefits of technology

It significantly improves the room temperature plasticity and high temperature strength of TiAl-based composite materials, enhances brittle fracture performance, and achieves lightweight and high strength, making it suitable for new energy vehicles, drones, aerospace and humanoid robots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669965B_ABST
    Figure CN121669965B_ABST
Patent Text Reader

Abstract

This invention provides a method for preparing a high-entropy alloy TPMS network-reinforced TiAl-based composite material and its application, relating to the field of metal matrix composite technology. The method includes the following steps: firstly, preparing TiAlV with a TPMS network structure using selective laser melting technology. 0.5 A high-entropy alloy of CrMo was prepared by filling the voids in its TPMS network structure with TiAl4822 powder, followed by vacuum hot pressing sintering. The resulting composite material contained TiAlV... 0.5 The CrMo phase is uniformly distributed in the matrix in a continuous TPMS network. The above technical solution introduces TiAlV into the TiAl matrix. 0.5 The TPMS network structure of the CrMo high-entropy alloy achieves an organic combination of structural design and performance control, endowing the composite material with higher room temperature and high temperature strength, better toughness and thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal matrix composites technology, and more particularly to a method for preparing a TiAl-based composite material reinforced with a high-entropy alloy TPMS network and its application. Background Technology

[0002] With the continuous pursuit of performance limits in high-end equipment fields such as aerospace and defense industries, almost stringent requirements have been placed on the structural materials of key hot-end components: they must possess excellent specific strength, high specific stiffness, and outstanding creep resistance under extreme high-temperature environments, while simultaneously meeting stringent lightweighting targets. Traditional titanium alloys and nickel-based superalloys face bottlenecks in such applications: the former has limited temperature resistance, while the latter, although resistant to high temperatures, has a significantly higher density, making it difficult to simultaneously balance high-temperature performance and weight reduction requirements.

[0003] Against this backdrop, it also possesses low density (approximately 3.7-4.3 g / cm³). 3 TiAl-based intermetallic compounds, with their high-temperature resistance (up to 1000℃ and above), are considered one of the most promising next-generation lightweight high-temperature structural materials, showing great promise in achieving higher efficiency and lighter weight in equipment. However, the inherent brittleness of TiAl-based alloys leads to low room-temperature ductility and damage tolerance, making them prone to brittle fracture, which severely restricts their engineering application in complex components.

[0004] To address the aforementioned bottlenecks, modifying the TiAl matrix by adding alloying elements such as Nb has become a key technical approach to improve material properties. The solid solution strengthening, grain refinement strengthening, and β-phase stabilization effects of Nb can effectively improve the room-temperature plasticity and high-temperature strength of the alloy. However, this technical approach faces a dual challenge: First, the amount of Nb added needs to be precisely controlled. Excessive introduction not only forms brittle phases (such as NbAl3), impairing mechanical properties, but also weakens the material's lightweight advantage due to Nb's high density. Second, and more critically, traditional casting or powder metallurgy processes easily lead to macro / micro-level agglomeration of Nb, making it difficult to achieve a uniform and continuous distribution of the strengthening phase. This hinders the stable and full realization of its alloying improvement effect, becoming a major technical obstacle to synergistically improving the properties of TiAl alloys through Nb elementation.

[0005] In view of this, it is necessary to design an improved method for preparing high-entropy alloy TPMS network-reinforced TiAl-based composite materials and their applications to solve the above problems. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a high-entropy alloy TPMS network-reinforced TiAl-based composite material and its application.

[0007] To achieve the above-mentioned objectives, in a first aspect, the present invention provides a method for preparing a TiAl-based composite material reinforced with a high-entropy alloy TPMS network, comprising the following steps:

[0008] S1, TiAlV 0.5 CrMo powder is filled into the SLM powder supply hopper, and the TC4 substrate is placed stably on the molding stage; after inert gas is introduced into the molding chamber, the TC4 substrate is heated to 300-600℃.

[0009] S2. The TiAlV in the SLM powder supply hopper 0.5 CrMo powder was deposited on a TC4 substrate, and selective laser melting technology was used to selectively scan and melt the deposited powder layer. The above process of depositing powder and scanning melting was repeated to obtain a pre-alloy with a three-dimensional TPMS network structure.

[0010] S3. Fill the network structure of the pre-alloy obtained in step S2 with TiAl4822 powder and pre-compact it to obtain a composite blank; perform hot pressing sintering on the composite blank to obtain the TiAl-based composite material.

[0011] Preferably, in step S2, the process parameters for selective scanning melting are: laser power 70-100W, scanning speed 600-1100mm / s, scanning spacing 60μm, single layer thickness 25μm, rotation angle of adjacent layer scanning path 60-90°, and fan power 5-7W.

[0012] Preferably, in step S3, the hot pressing sintering process is carried out under a vacuum degree of not less than 1×10⁻⁶. -2 The process is carried out under a protective atmosphere of Pa or argon, at a temperature of 1100-1250℃, for a time of 30-120 minutes, and at a hot pressing pressure of 20-50 MPa.

[0013] Preferably, in step S1, TiAlV 0.5 The CrMo powder particles are nearly spherical with an average particle size of 15-53 μm. The particle size distribution is D10≤20.2 μm, D50≤35.8 μm, and D90≤49.6 μm. The chemical composition is as follows: Ti 33.0-35.0 wt.%, Al 30.0-32.0 wt.%, V 14.0-16.0 wt.%, Cr 9.0-11.0 wt.%, Mo 9.0-11.0 wt.%. The impurity content is controlled as follows: O≤0.08 wt.%, C≤0.02 wt.%, N≤0.02 wt.%, H≤0.005 wt.%, Fe≤0.10 wt.%, Ni≤0.05 wt.%.

[0014] Preferably, in step S3, the TiAl4822 powder particles are spherical with an average particle size of 15-53 μm and a particle size distribution of D10≤18.2 μm, D50≤38.6 μm, and D90≤50.8 μm. The chemical composition is as follows: Al 32.4-33.6 wt.%, Cr 2.4-2.8 wt.%, Nb 4.5-5.1 wt.%, O≤0.08 wt.%, C≤0.02 wt.%, N≤0.02 wt.%, H≤0.005 wt.%, Fe≤0.10 wt.%, Ni≤0.05 wt.%, with the balance being Ti.

[0015] Preferably, the laser power is 80-90W and the scanning rate is 800-900mm / s.

[0016] Preferably, the sintering temperature is 1150-1200℃, the time is 60-90min, and the hot pressing pressure is 30-45MPa.

[0017] In a second aspect, the present invention provides a TiAl-based composite material reinforced with a high-entropy alloy TPMS network, comprising:

[0018] Matrix: Its composition is TiAl4822;

[0019] Enhanced phase: It is a TiAlV with a TPMS network structure. 0.5 A CrMo high-entropy alloy with a porosity of 30-90% is dispersed in the matrix, and the pore diameter of the TPMS network structure is 0.5-3 mm.

[0020] Preferably, the composite material has the following properties at room temperature:

[0021] Tensile strength is 820-850 MPa;

[0022] The yield strength is 730-760 MPa;

[0023] Elongation rate 8-10%;

[0024] The reduction of area is 12-14%, and its elongation is not less than 8% in the range of 200-600℃.

[0025] Thirdly, this invention provides an application of high-entropy alloy TPMS network-reinforced TiAl-based composite material in the fields of new energy vehicles, drones, aerospace and humanoid robots.

[0026] The beneficial effects of this invention are:

[0027] 1. The high-entropy alloy TPMS network-reinforced TiAl-based composite material provided by this invention is prepared by first using selective laser melting technology to prepare TiAlV. 0.5The TPMS network structure of the CrMo high-entropy alloy was obtained by vacuum hot pressing sintering. TiAlV was selected as the alloy. 0.5 CrMo high-entropy alloys, as reinforcing phases in composite materials, can significantly improve the room-temperature plasticity and comprehensive mechanical properties of the TiAl matrix while maintaining the overall lightweight of the material; in addition, TiAlV... 0.5 CrMo exhibits good compatibility with the TiAl matrix in terms of chemical composition and crystal structure, which helps to form a stable metallurgical interface and avoids the formation of brittle reactive phases. Meanwhile, TiAlV... 0.5 The high plasticity of CrMo is beneficial to improving the brittleness of TiAl alloys. By designing the high-entropy alloy as a continuous triple-period minimum surface network (TPMS) structure, efficient load transfer and uniform stress distribution can be achieved, thereby significantly improving the fracture toughness and ductility of TiAl alloys.

[0028] 2. Structural advantages of the TPMS proposed in this invention: In the selective laser melting (SLM) forming process, the forming mechanism of the TPMS structure mainly stems from its continuous and smooth minimum surface feature. This structure avoids geometrical abrupt changes at traditional rods or nodes, allowing loads and thermal stresses to be uniformly transferred along the curved surface during forming, thereby effectively reducing local stress concentration and improving the overall stress state. Simultaneously, the uniform stress and temperature distribution helps alleviate the thermo-mechanical coupling instability generated during rapid melting-solidification, providing a foundation for stable forming. Furthermore, the continuously changing curved surface of the TPMS structure forms a natural self-supporting geometry in the construction direction, with its local overhang angle generally smaller than the critical forming angle allowed by the SLM process. This allows the molten layers to be stably stacked layer by layer based on the formed entity, rather than relying solely on loose powder support, fundamentally avoiding the collapse, warping, and local deformation problems that easily occur in horizontal rods in truss-like structures. In addition, the self-supporting forming behavior also facilitates the stable spreading and uniform solidification of the molten pool, reduces the generation of forming defects, and significantly improves the forming stability and overall forming quality of complex porous structures.

[0029] 3. The preparation method proposed in this invention involves introducing continuously distributed TiAlV into a TiAl4822 matrix. 0.5 The TPMS network structure of a CrMo high-entropy alloy, combined with selective laser melting (SLM) and high-pressure sintering (HPS) processes, significantly improves the material's microstructure uniformity and interfacial bonding strength. Furthermore, by adjusting the process parameters of SLM and HPS, this invention enables the high-entropy alloy phase to form a continuous and uniform reinforcing network within the matrix. Simultaneously, the porosity of the TPMS structure can be controllably adjusted, achieving a balance between high strength and lightweight characteristics. The resulting composite material exhibits higher room-temperature and high-temperature strength, superior toughness and thermal stability, while maintaining a relatively low density (approximately 3.9-4.3 g / cm³). 3This significantly improves the overall mechanical properties and application reliability of TiAl-based alloys.

[0030] 4. The preparation method proposed in this invention, by employing high-precision selective laser melting technology and powder metallurgy combined with interface reaction control process, can achieve high-quality composite of high-entropy alloy TPMS structure and TiAl matrix, ensuring the continuous, uniform and stable distribution of reinforcing phase, thereby improving the plasticity of TiAl alloy to meet its application in the fields of new energy vehicles, drones, aerospace and humanoid robot technology. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the preparation process of the high-entropy alloy TPMS network-reinforced TiAl-based composite material proposed in this invention;

[0032] Figure 2 This is a schematic diagram of the structure of the TiAl-based composite material proposed in this invention;

[0033] Figure 3 TiAlV in the TiAl-based composite material prepared in Example 1 of this invention 0.5 SEM image of the junction between CrMo and TiAl4822. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] It should also be noted that, in order to avoid obscuring the present invention with unnecessary details, only the structures and / or processing steps closely related to the present invention are shown in the accompanying drawings, while other details that are not closely related to the present invention are omitted.

[0036] Additionally, it should be noted that the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0037] On one hand, the present invention provides a TiAl-based composite material reinforced with a high-entropy alloy TPMS network, comprising:

[0038] Matrix: Its composition is TiAl4822;

[0039] Enhanced phase: It is a TiAlV with a TPMS network structure. 0.5 CrMo high-entropy alloy, made from TiAlV 0.5CrMo is prepared by laser melting, with a porosity of 30-90%, and is dispersed in the matrix; the pore diameter of the TPMS network structure is 0.5-3 mm. Specifically, it is of the Gyroid, Schwarz D, or Diamond type.

[0040] The above-mentioned composite material has the following properties at room temperature:

[0041] Tensile strength is 820-850 MPa;

[0042] The yield strength is 730-760 MPa;

[0043] Elongation rate 8-10%;

[0044] With a reduction of area of ​​12-14% and an elongation of not less than 8% in the range of 200-600℃, TiAl-based composite materials with the above properties can be applied to new energy vehicles, drones, aerospace and humanoid robots.

[0045] In the above technical solution, TiAlV is selected. 0.5 CrMo, as a high-entropy alloy reinforcing phase, uses Ti and Al as its main framework elements and is highly compatible with the TiAl matrix, ensuring good matching with the TiAl matrix in terms of chemical composition and crystal structure. The introduction of multiple principal elements such as V, Cr, and Mo can significantly increase the mixing entropy of the system, suppress the formation of brittle intermetallic compounds, and promote the formation of stable solid solution phases, thereby improving the strength and thermal stability of the composite material. Furthermore, TiAlV... 0.5 The matching of CrMo and TiAl matrix in terms of lattice constant and thermal expansion coefficient enables them to form a stable metallurgical bond during sintering, avoiding interfacial stress concentration and reaction layer formation. This ensures that the high-entropy alloy TPMS network structure forms a continuous and uniform reinforcing network in the matrix, providing a reliable structural guarantee for the high strength and high toughness of the composite material.

[0046] In addition, by adopting TiAlV 0.5 The TPMS network structure of the CrMo high-entropy alloy reinforces the TiAl matrix, fully utilizing the excellent high-temperature strength and heat resistance of the high-entropy alloy to effectively improve the high-temperature mechanical properties of the TiAl matrix; furthermore, due to the TiAlV... 0.5 The density of CrMo high-entropy alloy is only 4.7 g / cm³. 3 The concentration is much lower than that of Nb, which ensures that the composite material maintains its lightweight characteristics, giving it both high strength, high toughness and lightweight properties.

[0047] Furthermore, this invention also provides a method for preparing the above-mentioned high-entropy alloy TPMS network-reinforced TiAl-based composite material, the specific preparation process of which is as follows: Figure 1 As shown, it includes the following steps:

[0048] S1, TiAlV 0.5 CrMo powder is filled into the SLM powder supply hopper, and the TC4 substrate is placed stably on the molding stage; after inert gas is introduced into the molding chamber, the substrate is heated to 300-600℃.

[0049] S2. The TiAlV in the SLM powder supply hopper 0.5 CrMo powder is laid on a TC4 substrate. Selective laser melting technology is used to selectively scan and melt the powder layer according to a preset three-dimensional model path. The above process of laying powder and scanning melting is repeated to obtain a pre-alloy with a three-dimensional TPMS network structure.

[0050] S3. After cooling the pre-alloy obtained in step S2 under an inert atmosphere, TiAl4822 powder is uniformly filled into the network structure voids of the pre-alloy and pre-compacted to obtain a composite billet; the composite billet is then subjected to hot pressing sintering to obtain the TiAl-based composite material.

[0051] In the above technical solution, by constructing TiAlV 0.5 By constructing a continuous TPMS network structure for CrMo high-entropy alloys and controlling its porosity, a synergistic optimization of reinforcement and lightweighting was achieved. The resulting composite material exhibits excellent high-temperature strength, thermal stability, and oxidation resistance, while maintaining a low density (approximately 3.9-4.3 g / cm³). 3 Compared to the density of conventional titanium alloy (Ti6Al4V) (approximately 4.4-4.8 g / cm³), this is significantly different. 3 While maintaining its lightweight characteristics, it significantly improves strength and toughness, and can be widely used in key components of aerospace engines, structural components of high-speed UAVs, hot-end systems of new energy vehicles, and joint drive components of high-performance humanoid robots.

[0052] In some embodiments, in step S1, the TC4 substrate serves as the molding carrier and structural template for the TPMS skeleton. Before use, it needs to be cleaned to remove oil stains, such as acetone, from its surface, and then dried and stored in an inert gas for later use. In other embodiments, substrates of other materials can also be used, as long as the corresponding purpose can be achieved, and this is not a limitation.

[0053] In some embodiments, in step S1, the inert gas is helium, argon, etc., preferably argon.

[0054] In some embodiments, in steps S1 and S3, TiAlV 0.5 Both CrMo powder and TiAl4822 powder need to be dried in a vacuum drying oven at 75±85℃ for 6-12 hours before use to avoid the influence of impurities such as water on the preparation process. Specifically, TiAlV0.5 The CrMo powder particles are nearly spherical with an average particle size of 15-53 μm. The particle size distribution is D10≤20.2 μm, D50≤35.8 μm, and D90≤49.6 μm. The chemical composition is as follows: Ti 33.0-35.0 wt.%, Al 30.0-32.0 wt.%, V 14.0-16.0 wt.%, Cr 9.0-11.0 wt.%, Mo 9.0-11.0 wt.%. The impurity content is controlled as follows: O≤0.08 wt.%, C≤0.02 wt.%, N≤0.02 wt.%, H≤0.005 wt.%, Fe≤0.10 wt.%, Ni≤0.05 wt.%. TiAl4822 powder particles are nearly spherical with an average particle size of 15-53 μm and a particle size distribution of D10≤18.2μm, D50≤38.6μm, and D90≤50.8μm. The chemical composition is as follows: Al 32.4-33.6 wt.%, Cr 2.4-2.8 wt.%, Nb 4.5-5.1 wt.%, O≤0.08 wt.%, C≤0.02 wt.%, N≤0.02 wt.%, H≤0.005 wt.%, Fe≤0.10 wt.%, Ni≤0.05 wt.%, with the balance being Ti. More specifically, TiAlV... 0.5 CrMo powder and TiAl4822 powder were prepared by high-purity inert gas atomization. After melting the alloy raw materials under vacuum induction melting conditions, they were atomized by high-pressure argon gas and rapidly cooled and solidified to form near-spherical powders. Then, they were dried in a vacuum drying oven at 60-80℃ for 6-12 hours, with a target oxygen content of O<500ppm.

[0055] In the above technical solution, by controlling the properties of the raw material powder within the above range, the precision of the TPMS network structure prepared by selective laser melting and the density of TiAl can be improved, thereby further improving the mechanical properties of the composite material.

[0056] In some embodiments, in step S2, the selective scanning melting process parameters are: laser power 70-100W, scanning speed 600-1100mm / s, scanning spacing 60μm, single-layer thickness 25μm, adjacent layer scanning path rotation angle 60-90°, and fan power 5-7W. Preferably, the laser power is 80-90W, and the scanning speed is 800-900mm / s. Under these conditions, the obtained three-dimensional TPMS network structure can achieve stable forming, and the surface of the pre-formed alloy sample shows no obvious cracks or collapse defects, the interlayer bonding is dense, and the overall forming quality exhibits superior and better consistency. In some embodiments, in step S3, the hot pressing sintering treatment is performed under a vacuum degree of not less than 1×10⁻⁶. -2The hot pressing is carried out under a protective atmosphere of Pa or high-purity argon, at a temperature of 1100-1250℃ for 30-120 min, with a pressure of 20-50 MPa and a heating rate of 5-10℃ / min from room temperature (25℃) to the target temperature. Preferably, the sintering temperature is 1150-1200℃ for 60-90 min, the hot pressing pressure is 30-45 MPa, and the heating rate is 8-10℃ / min. It should be noted that the purpose of the pre-compaction treatment before hot pressing sintering is to ensure that the TiAl4822 powder is fully filled in the gaps of the network structure. The specific conditions can be selected according to actual needs and are not limited here.

[0057] The preparation method and application of the high-entropy alloy TPMS network-reinforced TiAl-based composite material proposed in this invention will be further explained below with reference to specific embodiments:

[0058] Example 1

[0059] This embodiment prepares a high-entropy alloy TPMS network-reinforced TiAl-based composite material. The specific preparation method includes the following steps:

[0060] At 80℃, in a vacuum environment (<10 -2 Dry TiAl4822 powder and TiAlV in Pa) 0.5 CrMo powder for 8 hours; TiAl4822 powder and TiAlV 0.5 The original purity of CrMo powder is greater than 99.9%. The average particle size of TiAl4822 powder is 45 μm. Its chemical composition (wt.%) is: Al 32.4%, Cr 2.5%, Nb 4.6%, O 0.06%, C 0.015%, N 0.015%, H 0.002%, Fe 0.07%, Ni 0.04%, with the balance being Ti; TiAlV 0.5 The average particle size of the CrMo powder is 45 μm, and the density is 5.87 g / cm³. 3 Its chemical composition (wt.%) is: Ti 33.6%, Al 30.5%, V 14.8%, Cr 10.5%, Mo 9.8%, with the balance being impurities;

[0061] Using TC4 alloy as the substrate, with a thickness of 25mm and dimensions of 100mm×100mm, the surface is sandblasted, cleaned with acetone solution and dried, and then placed into the forming cavity of the EOS M290 selective laser melting system. Argon gas is introduced into the cavity to form a positive pressure protective environment to ensure that the oxygen content does not exceed 0.05ppm. By adjusting the distance between the substrate heating device and the substrate surface, the substrate can be heated uniformly and efficiently to achieve stable heat conduction. The substrate heating temperature is 400℃.

[0062] TiAlV substrate 0.5 CrMo powder was processed using selective laser melting (SLM). First, a three-dimensional Gyroid-type TPMS network structure was modeled and sliced. Based on this, process parameters such as scanning speed were set. Following a Diamond-type scanning path generated from the slices, the powder layer (30 μm thick) was selectively melted and shaped. The powder layers were selectively melted layer by layer using a high-energy laser. This process of powder layering and scanning / melting was repeated, with each powder layer being 30 μm thick. The specific number of layers could be adjusted according to actual conditions. The melted portion rapidly solidified and stacked layer by layer, ultimately forming a pre-alloy with a continuous network topology of Gyroid-type TPMS. The laser melting process parameters were as follows: laser power 80 W, scanning speed 700 mm / s, scanning spacing 60 μm, single-layer powder thickness 25 μm, adjacent layer scanning path rotation angle 90°, and fan power 7 W.

[0063] The pre-formed alloy is removed from the forming table by wire cutting. Residual powder and impurities within the structure are removed by compressed gas purging or ultrasonic cleaning to ensure unobstructed pores. The cleaned pre-formed alloy is then fixed in a mold, and TiAl4822 powder is uniformly filled into the structural voids using vibration-assisted vacuum infiltration to ensure thorough compaction, thus obtaining a composite preform. The composite preform is placed in an OTF-1200X-VHP vacuum hot pressing sintering furnace at a vacuum degree of not less than 1×10⁻⁶. -2 Under a protective atmosphere of Pa or high-purity argon, the temperature is increased to 1200℃ at a rate of 10℃ / min, hot pressing is applied at 30MPa and held at that temperature for 60min to achieve densification of the composite preform and TiAlV. 0.5 Metallurgical bonding of CrMo network structure yields TiAl-based composite materials, in which TiAlV... 0.5 The composition ratio of CrMo to TiAl4822 is 25:75 (mass fraction). It should be noted that, unless otherwise specified, the reagents and raw materials used in the embodiments of this invention can be obtained commercially.

[0064] The specific structure of the TiAl-based composite material prepared in this embodiment is as follows: Figure 2As shown, it exhibits an excellent balance between load-bearing capacity and toughness at room temperature, with an ultimate tensile strength of up to 830 MPa and a yield strength of approximately 750 MPa, significantly higher than the ultimate tensile strength (approximately 600 MPa) of TiAl4822 alloy prepared by traditional selective laser melting technology. Simultaneously, the composite material maintains a stable elongation of 8%, indicating good plastic deformation capacity, and its reduction of area (Z) reaches 12%, demonstrating excellent fracture toughness and energy absorption capacity. The SEM image of the interface of the TiAl-based composite material is shown below. Figure 3 As shown in the figure, the left side is TiAl4822 alloy, and the right side is TiAlV alloy. 0.5 The results showed that the CrMo alloy achieved a high-quality metallurgical composite with a clean interface and excellent bonding. Furthermore, the microstructures on both sides of the interface exhibited a stark contrast: the TiAl4822 alloy on the left displayed a uniform and smooth microstructure, while the TiAlV alloy on the right... 0.5 The CrMo alloy exhibits a complex network structure composed of lamellar layers of varying depths. Furthermore, the straight and narrow interface lines indicate that the interdiffusion of elements between the two alloys was effectively controlled during the composite preparation process, preventing the formation of excessively thick and potentially brittle diffusion reaction zones. This demonstrates that the composite preparation process not only achieves high-quality solid-state diffusion bonding or metallurgical bonding between the two TiAl alloys but also avoids introducing harmful interface phases or defects.

[0065] Example 2

[0066] This embodiment prepares a high-entropy alloy TPMS network-reinforced TiAl-based composite material. The specific preparation method includes the following steps:

[0067] At 80℃, in a vacuum environment (<10 -2 Dry TiAl4822 powder and TiAlV in Pa) 0.5 CrMo powder for 8 hours; TiAl4822 powder and TiAlV 0.5 The original purity of CrMo powder is greater than 99.9%. The average particle size of TiAl4822 powder is 45 μm. Its chemical composition (wt.%) is: Al 33%, Cr 2.5%, Nb 4.6%, O 0.06%, C 0.015%, N 0.015%, H 0.002%, Fe 0.07%, Ni 0.04%, balance Ti 0.05%, balance TiAlV. 0.5 The average particle size of the CrMo powder is 45 μm, and its chemical composition (wt.%) is: Ti 33.6%, Al 30.5%, V 14.8%, Cr 10.5%, Mo 9.8%, with the balance being impurities;

[0068] Using TC4 alloy as the substrate, with a thickness of 25mm and dimensions of 100mm×100mm, the surface is sandblasted, cleaned with acetone solution and dried, and then placed into the forming cavity of the EOS M290 selective laser melting system. Argon gas is introduced into the cavity to form a positive pressure protective environment to ensure that the oxygen content does not exceed 0.05ppm. By adjusting the distance between the substrate heating device and the substrate surface, the substrate can be heated uniformly and efficiently to achieve stable heat conduction. The substrate heating temperature is 400℃.

[0069] TiAlV substrate 0.5 CrMo powder was processed using selective laser melting (SLM). A three-dimensional Diamond-type TPMS network structure was modeled and sliced. A corresponding scanning trajectory was established based on process parameters such as scanning speed. The powder layers were selectively melted layer by layer according to the generated Diamond-type path. This process of selectively melting the powder layers with a high-energy laser was repeated, with the melted portion rapidly solidifying and stacking layer by layer to ultimately form a pre-alloy with a continuous Diamond-type TPMS network structure exhibiting continuous network topology. The laser melting process parameters were as follows: laser power 90W, scanning speed 1000mm / s, scanning spacing 60μm, single-layer powder thickness 25μm, adjacent layer scanning path rotation angle 67°, and fan power 7W.

[0070] The pre-formed alloy is removed from the forming table by wire cutting. Residual powder and impurities within the structure are removed by compressed gas purging or ultrasonic cleaning to ensure unobstructed pores. The cleaned pre-formed alloy is then fixed in a mold, and TiAl4822 powder is uniformly filled into the structural voids using vibration-assisted vacuum infiltration to ensure thorough compaction, thus obtaining a composite preform. The composite preform is placed in an OTF-1200X-VHP vacuum hot pressing sintering furnace at a vacuum degree of not less than 1×10⁻⁶. -2 Under a protective atmosphere of Pa or high-purity argon, the temperature is increased to 1100℃ at a rate of 10℃ / min, hot pressing of 50MPa is applied and held at that temperature for 90min to achieve densification of the composite preform and TiAlV. 0.5 Metallurgical bonding of CrMo network structure yields TiAl-based composite materials, in which TiAlV... 0.5 The composition ratio of CrMo to TiAl4822 is 30:70 (mass fraction ratio).

[0071] The composite material prepared in this embodiment exhibits an excellent balance between load-bearing capacity and toughness at room temperature. Its tensile strength can reach 840 MPa and its yield strength is about 750 MPa, which is significantly improved compared with traditional TiAl alloys. At the same time, the elongation of the composite material is stable at 10%, indicating that it has good plastic deformation capacity. The reduction of area (Z) of the composite material can reach 14%, showing excellent fracture toughness and energy absorption capacity.

[0072] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a high-entropy alloy TPMS network-reinforced TiAl-based composite material, characterized in that, Includes the following steps: S1, TiAlV 0.5 CrMo powder is filled into the SLM powder supply hopper, and the TC4 substrate is placed stably on the molding stage; after inert gas is introduced into the molding chamber, the TC4 substrate is heated to 300-600℃. S2. The TiAlV in the SLM powder supply hopper 0.5 CrMo powder was deposited on a TC4 substrate, and selective laser melting technology was used to selectively scan and melt the deposited powder layer. The above process of depositing powder and scanning melting was repeated to obtain a pre-alloy with a three-dimensional TPMS network structure. The process parameters for selective scanning melting are: laser power 70-100W, scanning speed 600-1100mm / s, scanning spacing 60μm, single layer thickness 25μm, rotation angle of adjacent layer scanning path 60-90°, and fan power 5-7W. S3. Fill the network structure of the pre-alloy obtained in step S2 with TiAl4822 powder and pre-compact it to obtain a composite preform; perform hot pressing sintering on the composite preform to obtain the TiAl-based composite material; the hot pressing sintering is performed under a vacuum degree of not less than 1×10⁻⁶. -2 The process is carried out under a protective atmosphere of Pa or argon, at a temperature of 1100-1250℃, for a time of 30-120 minutes, and at a hot pressing pressure of 20-50 MPa.

2. The preparation method according to claim 1, characterized in that, In step S1, TiAlV 0.5 The CrMo powder particles are nearly spherical with an average particle size of 15-53 μm. The particle size distribution is D10≤20.2 μm, D50≤35.8 μm, and D90≤49.6 μm. The chemical composition is as follows: Ti 33.0-35.0 wt.%, Al 30.0-32.0 wt.%, V 14.0-16.0 wt.%, Cr 9.0-11.0 wt.%, Mo 9.0-11.0 wt.%. The impurity content is controlled as follows: O≤0.08 wt.%, C≤0.02 wt.%, N≤0.02 wt.%, H≤0.005 wt.%, Fe≤0.10 wt.%, Ni≤0.05 wt.%.

3. The preparation method according to claim 1, characterized in that, In step S3, the TiAl4822 powder particles are spherical with an average particle size of 15-53 μm and a particle size distribution of D10≤18.2 μm, D50≤38.6 μm, and D90≤50.8 μm. The chemical composition is as follows: Al 32.4-33.6 wt.%, Cr 2.4-2.8 wt.%, Nb 4.5-5.1 wt.%, O≤0.08 wt.%, C≤0.02 wt.%, N≤0.02 wt.%, H≤0.005 wt.%, Fe≤0.10 wt.%, Ni≤0.05 wt.%, with the balance being Ti.

4. The preparation method according to claim 1, characterized in that, The laser power is 80-90W, and the scanning rate is 800-900mm / s.

5. The preparation method according to claim 1, characterized in that, The sintering temperature is 1150-1200℃, the time is 60-90min, and the hot pressing pressure is 30-45MPa.

6. A TiAl-based composite material reinforced with a high-entropy alloy TPMS network prepared by the preparation method according to any one of claims 1-5, characterized in that, include: Matrix: Its composition is TiAl4822; Enhanced phase: It is a TiAlV with a TPMS network structure. 0.5 A CrMo high-entropy alloy with a porosity of 30-90% is dispersed in the matrix, and the pore diameter of the TPMS network structure is 0.5-3 mm.

7. The composite material according to claim 6, characterized in that, The composite material exhibits the following properties at room temperature: Tensile strength is 820-850 MPa; The yield strength is 730-760 MPa; Elongation rate 8-10%; The reduction of area is 12-14%, and its elongation is not less than 8% in the range of 200-600℃.

8. The application of a high-entropy alloy TPMS network reinforced TiAl-based composite material prepared by the preparation method shown in any one of claims 1-5, or the high-entropy alloy TPMS network reinforced TiAl-based composite material as described in claims 6-7, in the fields of new energy vehicles, drones, aerospace and humanoid robots.

Citation Information

Patent Citations

  • Integrally-formed composite material structure based on three-dimensional printing and casting technology and preparation method of integrally-formed composite material structure

    CN120606092A

  • Additive manufacturing method based on micro-selective laser melting technology

    WO2025222482A1